(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2026)
This study aims to analyze the impact of AI-supported workflow management on human resource sustainability, and to uncover the mediating role of digital agility, applied at Rafidain Bank as the oldest and largest state-owned bank in Iraq, currently undergoing accelerated digital transformation that requires redesigning workflows using AI technologies. The research addresses a gap between the intelligent workflow solutions adopted by the bank and the level of sustainability of its human resources across justice, transparency, employee well-being, and economic efficiency. The study adopted a descriptive-analytical approach. The population consisted of (150) employees in managerial levels, while the sample reached (78) respondents holding managerial positions (Director, Assistant Director, Department Head, Division Head). A questionnaire was the main data-collection tool, and data were analyzed using descriptive statistics, correlation, regression, and path analysis to test mediation. The findings reveal a significant positive impact of AI-supported workflow management on HR sustainability, and that digital agility partially mediates this relationship, acting as a channel that converts AI capabilities into higher HR sustainability. The study offers recommendations, most notably institutionalizing digital agility, linking intelligent workflow solutions to HR sustainability indicators, and proposing a guiding model.